Is narrow band imaging accurate to differentiate between high-risk and low-risk vocal fold leukoplakia? A systematic review and meta-analysis - Mina Sarabi Jamab; Arezoo Aghakouchakzadeh; Seied Omid Keyhan; Hosein Rafiemanesh; Ahmadreza Mirzaei; Mina Teimouri Badeleh Dareh (Oral Oncology Reports)
Vocal fold leukoplakia (VFL) is a pre-cancerous lesion that its management is still a therapeutic dilemma due to the need for timely diagnosis of its nature. Narrow band imaging (NBI) seemed to be beneficial to evaluate VFL. The present review aimed to explore the diagnostic accuracy of NBI in differentiating between low-risk and high-risk VFLs.Thirteen studies met the criteria of this systematic review and 11 of them were included in meta-analysis. The pooled sensitivity and specificity of NBI were 78.02 % (95 % CI: 71.64 %–83.31 %) and 93.70 % (95 % CI: 89.23 %–39.39 %), respectively. Ni 2011 had higher diagnostic accuracy among three main NBI classifications.In conclusion, NBI appeared to be an accurate and useful endoscopic method for evaluating VFL lesions.